Genetics, Molecular Mechanisms and Deployment of Bacterial Blight Resistance Genes in Rice. (3rd July 2020) - Pradhan, S. K.; Barik, S. R.; Nayak, D. K.; Pradhan, A.; Pandit, E.; Nayak, P.; Das, S. R.; Pathak, H.
Abstract: Rice is the principal food crop for people in South and South-East Asia and is life for millions of rural households worldwide. Bacterial blight (BB) is a very common, widespread, and highly destructive disease of rice. By the introduction of nitrogen-responsive high-yielding rice varieties, there was many-fold increase in the productivity level of tropical rice in recent years. Continuous cropping of rice with high nitrogen use and general wet conditions aggravated the disease incidence. The cost of chemical control measures is high and often shows adverse effects on the environment. Development of host-plant resistance is therefore a preferred approach to control the disease. Evolution of pathogen differentiation in the Xanthomonas oryzae pv. oryzae (Xoo) isolates often causes the breakdown of resistance against the disease. Efforts to deploy R -genes combinations are more important for managing the disease. Durable and broad-spectrum resistance may be achieved in host plants by precise gene incorporation through gene-pyramiding approach. To date, 45 genes conferring resistance to this disease have been identified in rice. The gene-for-gene concept of resistance governs the race-specific interaction between the host and the Xoo strains. Plants have developed different intrinsic mechanisms to defend the pathogen invasion. The pathogen also evolves to produce effectors with variation to counter the patterns-triggered immunity and convert the host plants response for effector-triggered susceptibility. This review discusses the progress in the identification of resistance genes, mechanisms of resistance, and deployment of resistance genes for durable and stable resistance in rice.